Fiscal Policy Impact on Economic Growth in Nigeria: An Empirical Analysis - Hassan, Bello (Fakultas Pertanian, 2025)
Nigeria's economic paradox of sustained GDP growth alongside rising unemployment, poverty, and income inequality underscores the limitations of relying solely on headline economic indicators. While fiscal policy plays a crucial role in economic management, its effectiveness in fostering inclusive growth remains debatable. This study examines the impact of fiscal policy on economic growth and macroeconomic stability in Nigeria from 2003 to 2023, employing time-series data and econometric techniques such as regression analysis. The study evaluates the relationship between government expenditure, taxation, and income distribution, highlighting the structural inefficiencies that hinder fiscal effectiveness. Findings suggest that while fiscal policy has contributed to GDP growth, its impact is weakened by inefficient government spending, and revenue dependency, particularly on oil and institutional weaknesses. Moreover, fiscal interventions have failed to significantly reduce income inequality due to misallocation of resources and corruption. The study recommends targeted interventions to enhance fiscal policy effectiveness, including increased investment in human capital development, tax reforms, and improved governance. Strengthening fiscal discipline, diversifying revenue sources, and promoting transparency in public finance management are crucial for ensuring equitable and sustainable economic growth. These insights contribute to the broader discourse on the resource curse and the challenges of fiscal policy implementation in developing economies, offering valuable implications for policymakers in Nigeria and similar contexts.